The Level of Anxiety for the Elderly in Giving the Covid-19 Vaccine at the Central City Health Center - Abdul Wahab Pakaya; Fadly Syamsuddin; Lisdawati Mandrong; Syafrin U. Kumai; Atin Pateda (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
Corona Virus or currently known as Covid-19 is a type of virus that causes disorders of the respiratory tract to more severe diseases, such as Middle East Respiratory Syndrome (MERS-CoV) and Severe Acute Respiratory Syndrome (SARS-CoV) (Airlangga, 2020). Based on data from WHO and PHEOC of the Ministry of Health on April 13, 2021, the total confirmed cases of Covid-19 were 136,291,755. Cases with 2,941,128 deaths and have spread in 222 countries and 190 countries with local transmission (Emerging, 2021). Currently, in more than a year scientist have found a vaccine to help the body's immune system fight the corona virus, in Indonesia the COVID-19 vaccination target has reached 181.5 million people (Purbaya, 2021). One of the stages in this vaccination is the elderly with a target over 60 years. Anxiety is one of spectrum of emotional disorders that includes a combination of cognitive, emotional (feeling), and physical dysfunction. The spectrum of emotional disorders includes general emotional disorders, special emotional disorders (phobia, obsessive compulsive, panic, post-traumatic), sleep disorders, failure to recover, depression, bipolar disorder) (Geriatrics, 2020). Counseling will be given in the Pangmas project agenda. The Pangmas Project (community service) is one of the efforts made by the study program in an effort to improve public health through several programs implemented. Through this program, it is hoped that the elderly can find out 1) Covid-19 2) Covid-19 vaccines 3) Reduce anxiety in giving vaccinations.